2020
DOI: 10.1017/aer.2019.153
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of degradation equivalent operating time for aircraft gas turbine engines

Abstract: This paper presents a novel method for quantifying the effect of ambient, environmental and operating conditions on the progression of degradation in aircraft gas turbines based on the measured engine and environmental parameters. The proposed equivalent operating time (EOT) model considers the degradation modes of fouling, erosion, and blade-tip wear due to creep strain, and expresses the actual degradation rate over the engine clock time relative to a pre-defined reference condition. In this work, the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The details of the simulation methods can be found in [13]. Cranfield software Pythia [14][15] on gas turbine performance, gas path diagnostics and life consumption analysis is used for this research.…”
Section: Gas Turbine Performance Modelmentioning
confidence: 99%
“…The details of the simulation methods can be found in [13]. Cranfield software Pythia [14][15] on gas turbine performance, gas path diagnostics and life consumption analysis is used for this research.…”
Section: Gas Turbine Performance Modelmentioning
confidence: 99%
“…Zhou et al [25] calculated the combined effect of creep and fatigue on the first turbine stage of a power-generation gas turbine engine using the Larson-Miller Parameter and stress-life curve for the two damage mechanisms, respectively. Alozie et al [26] translated the effect of fouling and erosion on an HPT to an equivalent time that the engine would have to operate in a reference mission to suffer the same degradation as when exposed to desert sand.…”
Section: Performance-based Gas Turbine Lifing Studiesmentioning
confidence: 99%
“…The values of exponent magnitudes for the first, second, and third stages of the compressor are 2.5, 2.8571, and 2.3333, respectively. Alozie et al [49] reported a novel "equivalent operating time (EOT)" model that considers fouling, erosion, and blade-tip wear to determine the degradation rate of the turbine engine with respect to a pre-defined reference condition. It was concluded that the model perfectly predicts the component degradation and its remaining service life.…”
Section: Erosion Of Compressor Blades By Sand Particlesmentioning
confidence: 99%